QUALITATIVE RESEARCH METHODOLOGY IN EDUCATION - Ranbir Singh Malik (Jurnal Edubio Tropika, 2013)
Qualitative research is exploratory as its purpose is to discover new ideas and insights or even generate new theories. It focuses on understanding the particular and the distinctive and does not necessarily seek to generalize findings to other contexts. Researcher do not define specific research questions at the outset of the study, as doing so would likely impose their own framework on the research context. Collecting, analyzing and interpreting data are done largely simultaneously, with researcher constantly moving back and forth until new information does not add to their understanding of a topic, a point called data saturation. In fact data analysis steers data collection. Five stages of doing qualitative research; a) Choosing research sites and sample populations; b) Obtaining and encoding quailtative data (taking field notes); c) Preparing for and under taking focused interviews; d) Developing and maintaining field relations; and e) Organizing and analyzing the qualitative data gathered.